2020
DOI: 10.3390/su12166627
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Collaborative Logistics Using Specialist Planning Algorithms and a Gain-Sharing Business Model: A UK Case Study

Abstract: This paper introduces the FreightShare Lab Platform (FSLP) and its embedded business model, aiming to facilitate and encourage horizontal collaboration in freight logistics. The idea of the FSLP is to create collaborating clusters of freight operators, and corresponding collaborative operational plans, via specialised decision support algorithms and multi-fleet optimisation. Further, a gain-sharing business model embedded within the FSLP algorithms ensures that participants, mainly logistics service providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Given the great advancements in Information and Communication Technologies (ICTs), more complex technologies and concepts for information sharing were studied, e.g., blockchain technology [42], and the physical internet [43]. Recently, the success factors of collaborative business models have become an important topic, especially for urban logistics [16,17,44,45]. This demonstrates the merits of the current work because it considers barriers related to CTN business models that have not been sufficiently considered by previous works.…”
Section: Search Strategy and Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Given the great advancements in Information and Communication Technologies (ICTs), more complex technologies and concepts for information sharing were studied, e.g., blockchain technology [42], and the physical internet [43]. Recently, the success factors of collaborative business models have become an important topic, especially for urban logistics [16,17,44,45]. This demonstrates the merits of the current work because it considers barriers related to CTN business models that have not been sufficiently considered by previous works.…”
Section: Search Strategy and Resultsmentioning
confidence: 87%
“…Despite their merit, these studies have not provided a wider perspective of the barriers by considering specific CTN solutions and/or have not mentioned some important barriers, e.g., the barriers related to the CTN business model. Knowledge of these barriers is of great value since the failure or limited success of CTNs can be strongly attributed to the fundamentals of the business model [15][16][17]. In addition, these studies as well as exiting literature rarely identified a framework that systematically guides the decisions to implement the CTN with consideration to barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Habibi et al (2018) addressed collaborative problems of PI-hubs location and regarded cost-sharing as a possible solution for collaboration in the PI. Effective methodology for designing collaborative rules (Lafkihi et al , 2020) and platform incorporating a set of strategies on collaboration (Vargas et al , 2020) was developed to motivate collaboration in the freight transport network. Specifically, information sharing is the crucial component of collaboration in the PI.…”
Section: Resultsmentioning
confidence: 99%
“…The theme mainly involves the supply chain service industry, such as transport service providers (Simmer et al , 2017; Vargas et al , 2020; Plasch et al , 2021). In terms of characteristics of the PI, investigations on effective collaboration strategies are the first step of enterprises sharing assets (Lafkihi et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The development of logistics information platform, especially after the active sharing economy, has attracted many scholars to carry out related research, but its research still focuses on the construction technology of logistics information platform [16], system structure [17,18] and application mode [19,20]. Although research on its operation has gradually emerged in recent years, such as the emergence of pricing [21] and auction mechanisms [22], especially business matching based on logistics information platforms, and discovery algorithms (such as matching) [23][24][25], but few people are involved in the research on response after logistics business discovery.…”
Section: Introductionmentioning
confidence: 99%